The method of intellectual reformation in al-Faruqi’s epistemology - Shogar, Ibrahim (2019)
Reformation of Islamic thought has been the major objective of the contemporary Muslim scholarship. It aims at reviving fundamentals of Islamic thought and renewing the basic concepts of the Islamic worldview. Although the major problem of the Ummah has defined as “epistemological”, i.e., related to knowledge and intellectual stagnation, however the major challenge that has been facing the contemporary Muslim reformers is centered around the practical methods and effective mechanisms for intellectual reformation. A careful study of al-Faruqi’s thought may inspire the mind for some methodological hints to deal with such a complex problem. The main objective of this paper is to examine the above presupposition and formulate some methodological guidelines to understand al-Faruqi’s epistemology for reformation purposes. Al-Faruqi establishes his epistemology on thorough identification of two sets of principles for understanding the world: first, the theoretical principles which constitute the foundation of human knowledge; and the second is principles of values which are related especially to morality, religion, and culture. This paper has analyzed both types to uncover the integrated method of al-Faruqi’s epistemology. Fundamentals of Islamic epistemology and method of intellectual reformation in al-Faruqi’s epistemology are presented.